Influence of Brand Image on The Purchase Decision of Drinking Water in Packed Le Mineral (Case Study on Le Mineral Consumen in Karawang) - Anggi Fitriani Ramadani; Ajat Sudrajat (Fakultas Bisnis, 2022)
Bottled water companies have more and more competitors and continue to grow, resulting in companies having to create a good image of a brand in order to get a positive impression in the eyes of consumers. Because brand image is a factor that can influence consumer purchasing decisions. A good brand image will have a positive impact on the company which will ultimately benefit the company through increased purchases. This study aims to determine the effect of Brand Image on the Purchase Decision of Le Minerale bottled drinking water in the Karawang area. This study used descriptive and verification methods with a quantitative research approach. The sampling technique of this research is probability sampling using the formula Hair et all. The types of data used in this study are primary and secondary data. The data is processed using SPSS (Statistical Product and Service Solution) software . The results of this study prove that Brand Image has a significant effect on purchasing decisions.